Advanced in Molecular Mechanisms of Atherosclerosis: From Lipids to Inflammation - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Atherosclerosis is a leading cause of vascular disease worldwide. During the past several decades, landmark discoveries in the field of vascular biology have evolved our understanding of the biology of blood vessels and the pathobiology of local and systemic vascular disease states and have led to novel disease-modifying therapies for patients. This review is made to understand the molecular mechanism of atherosclerosis for these future therapies.CONTENT: Advances in molecular biology and -omics technologies have facilitated in vitro and in vivo studies which revealed that blood vessels regulate their own redox milieu, metabolism, mechanical environment, and phenotype, in part, through complex interactions between cellular components of the blood vessel wall and circulating factors. Dysregulation of these carefully orchestrated homeostatic interactions has also been implicated as the mechanism by which risk factors for cardiopulmonary vascular disease lead to vascular dysfunction, structural remodeling and, ultimately, adverse clinical events.SUMMARY: Atherosclerosis is a heterogeneous disease, despite a common initiating event of apoB-lipoproteins. Despite of acute thrombotic complications, an adequate resolution response is mounted, where efferocytosis prevents plaque necrosis and a reparative scarring response (the fibrous cap) prevents plaque disruption. However, a small percentage of developing atherosclerotic lesions cannot maintain an adequate resolution response, which leading to the formation of clinically dangerous plaques that can trigger acute lumenal thrombosis and tissue ischemia and infarction.KEYWORDS: atherosclerosis, oxidative stress, inflammation, efferocytosis, foam cells, thrombosis